The emerging role of histone deacetylase (HDAC) inhibitors in urological cancers - Sharma, Naomi L.; Groselj, Blaz; Hamdy, Freddie C.; Kiltie, Anne E. (BJU international, 2013)
What's known on the subject? and What does the study add? A growing body of evidence supports the anti‐cancer effect of histone deacetylase inhibitors (HDACi) in vitro, via multiple pathways, and many Phase I clinical trials have shown them to be well‐tolerated in a range of malignancies. Combined therapies, including with radiation, present an exciting area of current and planned study. This review summarises the evidence to date, including pre‐clinical data and clinical trials, of the anti‐cancer effect of HDACi in urological cancers. It provides an overview of epigenetics and the mechanisms of action of HDACi. It suggests areas of future development, including the current challenges for the successful introduction of HDACi into clinical therapy. Epigenetic modifications are known to play a critical role in the development and progression of many cancers. The opposing actions of histone deacetylases (HDACs) and histone acetyltransferases (HATs) modify chromatin and lead to epigenetic gene regulation, in addition to wider effects on non‐histone proteins. There is growing interest in the clinical application of HDAC inhibitors (HDACi) in cancer. HDACi have been shown to inhibit cancer cell growth both in vitro and in vivo and recent clinical trials have shown encouraging results in various urological cancers. In this review, we discuss the existing evidence and potential role for HDACi in urological malignancies, including in combined therapies.